Characteristic and Knowledge among Treatment Supporter of Children Patients with Tuberculosis at Lung Clinic Bandung OctoberâNovember 2012 - Suhada, Kamelia Utami; Sari, Sri Yusnita Irda; Wulandari, Diah Asri; Setiawati, Elsa Pudji (Althea Medical Journal, 2015)
Background: Children are the most vulnerable to get TB infection and infected by adult patients. One ofÂ the components of Directly Observed Treatment Short Course (DOTS) is direct observation by treatmentÂ supporter who has important role in the success of TBâs treatment. The aim of this study was to identifyÂ the characteristics and knowledge among treatment supporter of children patients with TB at Lung ClinicÂ Bandung.Methods: A descriptive study was conducted in October-November 2012 to 96 treatment supporters of childÂ patients who were diagnosed with TB, either new or old cases. They were selected by consecutive samplingÂ at Lung Clinic Bandung. Validated questionnaire with 14 questions was administered. The percentage ofÂ the correct answers was categorized as good, moderate, and poor. The Characteristic variables includedÂ age, sex, education, occupation, relation with the patients, living at the same house, presence of other TBÂ patients, and counseling given by providers. Data was analyzed using frequency distribution.Result: Most of the respondents were 21-30 years old (42.7%), female (84.4%), elementary school graduateÂ (33.3%), unemployed (69.8 %), mother of the child, living in the same house, had other TB patients, andÂ had received counseling by providers at Lung Clinic. The knowledge about TB among the respondents wasÂ moderate (56.3%). The respondents who had good knowledge had underwent the counseling session.Conclusions: The knowledge of the respondents was moderate. Further study on the relationship betweenÂ the level of knowledge of treatment supporter and the adherence of TB treatment should be conducted.Â [AMJ.2015;2(1):167â71]